Brain Structural Correlates of Odor Identification in Mild Cognitive Impairment and Alzheimer’s Disease Revealed by Magnetic Resonance Imaging and a Chinese Olfactory Identification Test - Wu, Xingqi; Geng, Zhi; Zhou, Shanshan; Bai, Tongjian; Wei, Ling; Ji, Gong-Jun; Zhu, Wanqiu; Yu, Yongqiang; Tian, Yanghua; Wang, Kai (Frontiers in Neuroscience, 2019)
Alzheimer's disease (AD) is a common memory-impairment disorder frequently accompanied by olfactory identification (OI) impairments. In fact, OI is a valuable marker for distinguishing AD from normal age-related cognitive impairment and may predict the risk of mild cognitive impairment (MCI)-to-AD transition. However, current olfactory tests were developed based on Western social and cultural conditions, and are not very suitable for Chinese patients. Moreover, the neural substrate of OI in AD is still unknown. The present study investigated the utility of a newly developed Chinese Smell Identification Test (CSIT) for OI assessment in Chinese AD and MCI patients. We then performed a correlation analysis of gray matter volume (GMV) at the voxel and region-of-interest (ROI) levels to reveal the neural substrates of OI in AD. Thirty-seven AD, 27 MCI, and 30 normal controls (NCs) completed the CSIT and MRI scans. Patients (combined AD plus MCI) scored significantly lower on the CSIT compared to NCs (F (2, 91) = 62.597, p < 0.001). Voxel-level GMV analysis revealed strong relationships between CSIT score and volumes of the left precentral gyrus and left inferior frontal gyrus (L-IFG). In addition, ROI-level GMV analysis revealed associations between CSIT score and left amygdala volumes. Our results suggest the following: 1) OI, as measured by the CSIT, is impaired in AD and MCI patients compared with healthy controls in the Chinese population; 2) the severity of OI dysfunction can distinguish patients with cognitive impairment from controls and AD from MCI patients; and 3) the left-precentral cortex and L-IFG may be involved in the processing of olfactory cues.